2016
DOI: 10.1080/02643294.2016.1188065
|View full text |Cite
|
Sign up to set email alerts
|

What can errors tell us about body representations?

Abstract: After an organism is touched, various processes need to occur to accurately localize touch on the body. In this review, we examine how tactile misperceptions can provide evidence regarding the functional organization of body representations. First, we propose that tactile detection and localization are serial processes, in contrast to hypotheses that propose separable parallel processes based on patients with numbsense. Second, we discuss how information in primary somatosensory maps project to representations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 146 publications
2
16
0
Order By: Relevance
“…Every deviation from the published protocol (Viceconti et al, 2018) or added procedure were declared. Neuroscientists (ML, AG, MP) and physiotherapists (AV, DL, DP, DR, GR, MT) constituted an inter-professional and interdisciplinary research team with both clinical and scientific background to better approach, from a rehabilitative perspective, a research area that has been historically treated by neuropsychological disciplines (Head and Holmes, 1911;Haggard and Wolpert, 2005;Medina and Coslett, 2016b). In agreement with the concept of a "literature map, " the results are graphically presented in Figures 3-8.…”
Section: Methodssupporting
confidence: 56%
See 2 more Smart Citations
“…Every deviation from the published protocol (Viceconti et al, 2018) or added procedure were declared. Neuroscientists (ML, AG, MP) and physiotherapists (AV, DL, DP, DR, GR, MT) constituted an inter-professional and interdisciplinary research team with both clinical and scientific background to better approach, from a rehabilitative perspective, a research area that has been historically treated by neuropsychological disciplines (Head and Holmes, 1911;Haggard and Wolpert, 2005;Medina and Coslett, 2016b). In agreement with the concept of a "literature map, " the results are graphically presented in Figures 3-8.…”
Section: Methodssupporting
confidence: 56%
“…Substantial differences exist between the two high-order processes represented by the somatoperception and somatorepresentation, from the basics mechanisms of the somatosensations . Despite these three different mechanisms are integrated and linked (Moseley et al, 2012), they may be dissociable, at least partially, because each one is based on different functional and neuroanatomical underlying structures and mechanisms: see for a review on the neural bases of body representations and Medina and Coslett (2016b) for descriptions of clinical cases highlighting this dissociation.…”
Section: Cognitive Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is adopted by several contributors to this issue. Medina and Coslett (2016) examine how errors in tactile perception inform us regarding how the brain represents the body. First, they discuss whether participants with numbtouchwho are thought to be able to localize touch without feeling touchprovide evidence in support of a double dissociation between processes for tactile detection and localization.…”
Section: Papers In This Issuementioning
confidence: 99%
“…Interestingly, even the localization of static, tactile events (e.g., a tap on the skin) is not always error-free. It has, for example, often been reported that a static tactile stimulus may be systematically misperceived at a different spatial location (Harrar & Harris, 2009;Ho & Spence, 2007;Longo, 2017;Mancini, Longo, Iannetti, & Haggard, 2011;Margolis & Longo, 2015;Steenbergen, Buitenweg, Trojan, & Veltink, 2014;Trojan et al, 2006; see Medina & Coslett, 2016, for a discussion). Even on the hand and fingers, locations that are very sensitive to two-point discrimination and localization (see Gallace & Spence, 2014;Stevens & Choo, 1996;Weinstein, 1968), systematic mislocalizations have been documented (e.g., Mancini et al, 2011;Margolis & Longo, 2015).…”
Section: Introductionmentioning
confidence: 99%